Mannose and phosphomannose isomerase regulate energy metabolism under glucose starvation in leukemia. Issue 12 (12th October 2021) - Saito, Yusuke; Kinoshita, Mariko; Yamada, Ai; Kawano, Sayaka; Liu, Hong‐Shan; Kamimura, Sachiyo; Nakagawa, Midori; Nagasawa, Syun; Taguchi, Tadao; Yamada, Shuhei; Moritake, Hiroshi
Abstract: Diverse metabolic changes are induced by various driver oncogenes during the onset and progression of leukemia. By upregulating glycolysis, cancer cells acquire a proliferative advantage over normal hematopoietic cells; in addition, these changes in energy metabolism contribute to anticancer drug resistance. Because leukemia cells proliferate by consuming glucose as an energy source, an alternative nutrient source is essential when glucose levels in bone marrow are insufficient. We profiled sugar metabolism in leukemia cells and found that mannose is an energy source for glycolysis, the tricarboxylic acid (TCA) cycle, and the pentose phosphate pathway. Leukemia cells express high levels of phosphomannose isomerase (PMI), which mobilizes mannose to glycolysis; consequently, even mannose in the blood can be used as an energy source for glycolysis. Conversely, suppression of PMI expression or a mannose load exceeding the processing capacity of PMI inhibited transcription of genes related to mitochondrial metabolism and the TCA cycle, therefore suppressing the growth of leukemia cells. High PMI expression was also a poor prognostic factor for acute myeloid leukemia. Our findings reveal a new mechanism for glucose starvation resistance in leukemia. Furthermore, the combination of PMI suppression and mannose loading has potential as a novel treatment for driver oncogene‐independent leukemia. Abstract : Leukemia cells utilize mannose as a glycolytic energy source under glucose starvation. High PMI expression is associated with poor prognosis in acute myeloid leukemia due to energy starvation resistance and anticancer drug resistance. Mannose load that exceeds the processing capacity of PMI inhibits leukemia cell proliferation and energy metabolism.